The impact of globalization on the Turkish economy - Eskinat, Rana (2007)
Turkey was one of the developing countries which adopted economic policies similar to Washington Consensus and tried to elevate the integration of Turkish Economy to the world Economy in 1980s. The aim of this study is to provide a detailed overview of the economic reform process since the beginning of 1980 and an assessment of whether these reforms were successful in terms of attaining their final objectives.